Ru-Ketu Tradition in the Modern Era: Challenges of Customary Law within Indonesia’s Rule-of-Law State Framework - Chatryen Dju Bire; Melinda Ratu Radja; Yossie Maria Yulianty Jacob; Raditya Maharani; Jenny Ermalinda; Mardiana Hasbullah (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2026)
Purpose: This study explores the role of the Ru-Ketu tradition within the framework of Indonesian law, focusing on the gap between its function as a living law and its declaratory status within the national legal system. Research Methodology: The research adopts an empirical legal method with a socio-legal approach in Sabu Raijua Regency, and the data were analyzed qualitatively through categorization and thematic interpretation of primary and secondary data. Results: The findings indicate that Ru-Ketu possesses a clear normative structure as an effective mechanism of social regulation in the Sabu society. However, its recognition at the national level remains largely declarative and is hindered by the dominance of positivist legal epistemology, internal religious dynamics, and folklorization risk. Conclusions: This study concludes that a more inclusive and dialogic legal approach is needed to bridge the gap between customary and state law. Such an approach should go beyond symbolic recognition toward substantive integration, enabling customary law like Ru-Ketu to function as living law within Indonesia’s plural legal system while maintaining its social legitimacy and normative role. Limitations: This study is limited to Sabu Raijua Regency; therefore, the findings are context-specific and reflect local socio-cultural conditions, and may not be fully generalizable to other customary law settings in Indonesia. Contributions: This study contributes to the discourse on legal pluralism by highlighting the discrepancy between formal recognition and substantive function and promoting a more substantive integration of living law into Indonesia’s national legal system.